Prothrombin Complex Concentrate Reduces Blood Product Utilization in Heart Transplantation. Issue 10 (18th October 2017) - Enter, Daniel H.; Zaki, Anthony L.; Marsh, Megan; Cool, Nikki; Kruse, Jane; Li, Zhi; Andrei, Adin‐Cristian; Iddriss, Adam; McCarthy, Patrick M.; Malaisrie, S. Chris; Anderson, Allen; Rich, Jonathan D.; et al.
Abstract : Background: Current practices for the reversal of warfarin before cardiac surgery include the use of vitamin K and fresh frozen plasma (FFP) to reduce the risk of bleeding. Although the 2010 International Society of Heart and Lung Transplantation guidelines acknowledge the use of prothrombin complex concentrate (PCC), there is no clear consensus on its efficacy. The objective of this study was to assess the efficacy of four‐factor (4‐F) PCC administration in patients requiring warfarin reversal before heart transplantation by determining blood product utilization perioperatively. Methods: Twenty‐one patients who received 4‐F PCC for warfarin reversal before heart transplantation were compared to a similar cohort of 39 patients who did not receive 4‐F PCC, from January 2011 to July 2015. Blood product utilization was collected retrospectively for the 24‐hour preoperative, intraoperative, and 48‐hour postoperative periods. Results: Patients receiving 4‐F PCC required fewer blood products in all three time periods. In the 24‐hour preoperative period, 22 (56%) patients in the control group and 2 (10%) patients in the 4‐F PCC groups received blood products (p<0.001). Intraoperatively, all patients received blood products. The 4‐F PCC group required fewer units of packed red blood cells (median 3 vs 7 units, p<0.001) and FFP (median 4 vs 9 units, p<0.001). In the 48‐hour postoperative period, 20 (51%) patients in the control group and 5 (24%) patients in the 4‐F PCC group received blood products (p=0.04). Conclusions: 4‐F PCC is associated with reduced blood product utilization 24 hours preoperatively and intraoperatively. Historically, the majority of patients require FFP for warfarin reversal preoperatively. In this single‐center study, a significant reduction in the need for FFP was demonstrated with the use of 4‐F PCC.